Study of concrete grade under stress using image provides by infrared thermography (IRT) - Mohammad Farhan, Abu Samah (2015)
Infrared thermography (IRT) has been used in the civil engineering field for different applications such as highway, bridge and concrete structures. Infrared have been using worldwide in non-destructive methods to evaluate bridges, building, highway pavement and airport. Previous research has shown that IRT can detect cracking, void and leaking on the structure. IRT systems provide a new non-destructive method to test every failure that occurs in the structure of building. Besides easy to perform, IRT also accurate and detail if the data required are supplied enough. With nowadays technological advances it is required to find a new method that are more users friendly. The main advantage of IRT than the others destructive testing techniques is that big scale areas can be scanned easily and practically with no need to destroy any building structure during testing. These will results to the main reduce in time, worker, work and machinery. The IRT device is no risky, as it does not release any radiation; it only records the infrared radiation release by the material that is under testing. The procedure is to scan the concrete cube under same stress and produce the infrared thermography image. This procedure will use different concrete's grade which are 25, 30, 35, 40, 45 and 50. Every changes of colour due to the load apply and difference grade of concrete will be recorded. Test was performed in the lab to have more quality image. All the data that been gather must be analysed using Colour Detector software and the result should be shown by using IRT analysis system.